A review on gene pyramiding of agronomic, biotic and abiotic traits in rice variety development - Ibrahim Silas Akos; Mohd Rafii Yusop; Mohd Razi Ismail; Shairul Izan Ramlee; Norazyah Abd Aziz Shamsudin; Asfaliza Binti Ramli; Bello Sani Haliru; Muhammad Ismai'la; Samuel Chibuike Chukwu (Hasanuddin University, 2019)
Rice Oryza sativa L is a staple food crop, and its seeds are the most important component part of the agronomic trait of the cereal crop, rich in nutrient and of economic value to human and even livestock. But, it is often threatened by various abiotic and biotic conditions that reduce the yield, because of high incidences of infectious disease agents and non-pathogenic conditions respectively. Pyramiding of the requisite resistance and tolerance genes into single elite high yielding variety of rice, confers wider spectrum of stress management, resulting to development of single multiline variety of rice. Marker-assisted selection utilizes DNA marker-linked primers for blast resistant gene (RM8225;Piz, RM6836;Piz, Pi2,Pi9), bacteria leaf blight (RM224; Xa-4, RM122;xa-5, RG136; xa-13, RM21;Xa-21) and drought tolerance (RM236;qDTY2.2, RM520;qDTY3.1, RM511;qDTY12.1) in pedigree, backcross and recurrent selection breeding methods. The objectives are to create awareness on the environmental safety of host-resistance, significance of single multiline resistance variety, effect of the interaction of stress conditions and associated simple sequence repeat (SSR) linked markers.